The Impact of Black Mold on Patienty Safety in The Emergency Department - Indriyanto, Sulistyo; Sutedja, Ade Armada; Ratnaningrum, Evi (Jurnal Riset Kesehatan, 2025)
Contamination by black mold in healthcare facilities can increase patient safety incidents through respiratory problems, allergic reactions, and healthcare associated infections. Enviromental factors such as high humidity and poor air quality support black mold growth. This study aimed to evaluate environmental conditions that potentially trigger black mold proliferation and their implications for patient safety in the Emergency Department (ED). An observational method was conducted by measuring temperature, humidity, and air quality from Juli-September 2025. An observational method was conducted by measuring temperature, humidity, and air quality from Juli-September 2025. Temperature and humidity were measured using the Thermo Hygrometer HTC-2, while air quality was assessed using the LKC-1000 Particle Counter in accordance with the Ministry of Health Regulation No.40 of 2022 and the World Health Organization Air Quality Guidelines 2021. The result showed that the ED environment contained conditions conducive to black mold growth. Room humidity ranged from 66,9% to 78,3%, exceeding the recomended standard of 60%. The PM2,5 concentration in the nurse station reached 19,4 µg/m3 higher than the WHO standard of 15 µg/m3. The findings emphasized the needs for corrective measures including increasing fresh air supply, improving ventilation system with at least 6 ACH, and implementing MERV13 air filtration to reduce environmental risk associated with black mold. In conclusion, the presence of black mold can threaten patient safety; therefore, hospital environmental management interventions are necessary to suppress mold growth.